ETIKA BISNIS SYARIAH DI ERA GLOBALISASI - Hamida Hunein; Sumarni S; Ahmad Subagyo (Media Riset Bisnis Manajemen Akuntansi, 2025)
Globalization has brought about significant transformations in the business world, characterized by market integration, cross-border capital flows, and technological advancements that accelerate transactions and the exchange of information. However, alongside these advancements arise various ethical challenges, including labor exploitation, economic inequality, and the dominance of materialistic values. In this context, Sharia business ethics emerges as a vital alternative, offering a value system rooted in Islamic principles—such as justice (‘adl), honesty (shidq), trustworthiness (amanah), and the prohibition of usury (riba), uncertainty (gharar), and gambling (maysir). This study aims to analyze the relevance of Sharia business ethics in addressing the challenges of globalization and to explore strategies for its application in contemporary business practices. The research employs a qualitative approach using library research, reviewing both classical and contemporary sources from Islamic and global literature relevant to business ethics and globalization. The analysis is conducted descriptively and interpretively, drawing upon Islamic ethical theories and the dynamics of the global market. The findings indicate that despite the significant challenges posed by globalization, Islamic ethical values remain relevant and can be adapted to modern business contexts. Sharia business ethics not only serves as a moral compass but also holds the potential to become the foundation of a sustainable, fair, and welfare-oriented business model.Keywords: Sharia business ethics, globalization, Islamic values, literature study, sustainable business.